DAMPAK INDUSTRIALISASI TERHADAP ASPEK SOSIAL EKONOMI MASYARAKAT - Endang Sutrisna (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2008)
Basically, development phenomena in Indonesian are indicated by unbalancedgrowth between the agrarian and industrial sector. That is not condusive for a better economicstructure. Industrialization is directed for sustaining development on economic growth, creatingsturdier economic structures, and production an economic sectors, support. Traditionaleconomy can be an alternative to stimulate industrial growth for wining competition, improvingindustrial productinity, and boosting the local traditional economy.